2013
DOI: 10.5964/ijpr.v7i1.114
|View full text |Cite
|
Sign up to set email alerts
|

Support-Seeking and Closeness Across Social Relationships: Relationship-General and Relationship-Specific Levels Analysis

Abstract: The current study examined whether interpersonal behaviors and perceptions could be conceptualized and measured as relationship-general versus relationship-specific tendencies. To address this goal, we examined (1) the similarities (or concordance) in support-seeking across individuals' social relationships and (2) how support-seeking may be related to relationship closeness at the relationship-general and relationship-specific levels. Participants were recruited from a regional university and granted course c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Seeking support is an effort made to seek help from those who are relevant to others to help to solve problems (Zartaloudi & Madianos, 2010). A study reported that patients who had problems were more likely to seek support from parents, friends, partners (Chow & Glaman, 2013). A study conducted for individuals who were depressed and anxious found that 47% sought support from professional experts to help solve their problems (Wallerblad, Möller, & Forsell, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Seeking support is an effort made to seek help from those who are relevant to others to help to solve problems (Zartaloudi & Madianos, 2010). A study reported that patients who had problems were more likely to seek support from parents, friends, partners (Chow & Glaman, 2013). A study conducted for individuals who were depressed and anxious found that 47% sought support from professional experts to help solve their problems (Wallerblad, Möller, & Forsell, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of my knowledge, no study has been found to specifically address support seeking in sibling relationships, namely viewing siblings as active participants in seeking support and their success in doing so. Despite being closely related to relationship closeness regardless of relationship type (parental, friend, and romantic), support seeking is not assessed as often as the amount and type of received support (Chow & Glaman, 2013). Individuals have a greater likelihood of receiving support in close relationships, which can also lead to greater feelings of closeness, particularly when the helper explicitly seeks out support (Barbee & Cunningham, 1995).…”
Section: Perceptions Of Sibling Support: B Factormentioning
confidence: 99%
“…Relationship closeness, defined as how emotionally connected one feels to another person, is often indicative of romantic relationship quality and feelings of emotional intimacy (Frost & LeBlanc, 2022;Van Bel et al, 2009). Furthermore, romantic partner closeness is associated with greater relationship commitment and satisfaction (Hassebrauck & Fehr, 2002) and higher perceptions of relationship support (Chow & Glaman, 2013). Closeness in romantic relationships may be particularly beneficial during emerging adulthood when many adults begin forming romantic relationships and experience new life stressors as adults (Gómez-López et al, 2019).…”
Section: Relationship Closeness As Protective Against Stress Reactivitymentioning
confidence: 99%